2013
DOI: 10.1089/neu.2012.2654
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in the Unresponsive Wakefulness Syndrome and Minimally Conscious State

Abstract: The goal of our study was to investigate different aspects of sleep, namely the sleep-wake cycle and sleep stages, in the vegetative state/unresponsive wakefulness syndrome (VS/UWS), and minimally conscious state (MCS). A 24-h polysomnography was performed in 20 patients who were in a UWS (n = 10) or in a MCS (n = 10) because of brain injury. The data were first tested for the presence of a sleep-wake cycle, and the observed sleep patterns were compared with standard scoring criteria. Sleep spindles, slow wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 38 publications
3
70
0
1
Order By: Relevance
“…115 A 24-h polysomnography study observed behavioural (eyes open or closed) but not electrophysiological sleep-wake patterns in VS. 116 Using high-density EEG, a homoeostatic decline of EEG slow-wave activity through the night (possibly reflecting residual synaptic plasticity) and periods of REM sleep (possibly reflecting 'dreaming') could be demonstrated in MCS but not in VS. 117 Event-related potentials (ERPs) are averaged EEG epochs to external or cognitive events. 118 In comatose patients, the absence of a cortical response to electrical stimulation of the median nerves during somatosensory ERP recordings is associated with poor outcome, especially after anoxic injury, 119 although treatment by hypothermia might challenge the prognostic utility of this approach.…”
Section: Electrophysiologymentioning
confidence: 99%
“…115 A 24-h polysomnography study observed behavioural (eyes open or closed) but not electrophysiological sleep-wake patterns in VS. 116 Using high-density EEG, a homoeostatic decline of EEG slow-wave activity through the night (possibly reflecting residual synaptic plasticity) and periods of REM sleep (possibly reflecting 'dreaming') could be demonstrated in MCS but not in VS. 117 Event-related potentials (ERPs) are averaged EEG epochs to external or cognitive events. 118 In comatose patients, the absence of a cortical response to electrical stimulation of the median nerves during somatosensory ERP recordings is associated with poor outcome, especially after anoxic injury, 119 although treatment by hypothermia might challenge the prognostic utility of this approach.…”
Section: Electrophysiologymentioning
confidence: 99%
“…Although recovery of the sleep-wake cycle is part of the criteria of UWS, recent studies have demonstrated an absence of electrophysiological characteristics of sleep in UWS [10,11]. Brain metabolism is usually diminished by 40 to 50% with impaired cortico-thalamo-cortical circuits but relatively preserved brainstem functions [12].…”
Section: Unresponsive Wakefulness Syndromementioning
confidence: 99%
“…Also, researchers have utilized EMG in an attempt to distinguish central from obstructive sleep apnea (SA) and concluded that the diaphragmatic EMG could be a useful technique in assessing neural respiratory drive and respiratory effort and, therefore, in accurately distinguishing the two forms of sleep apnea (SA). This is particularly relevant to the TBI population as, according to a report by Cologan et al [10], the majority of the events in their TBI sample were central in nature rather than obstructive, while in the general population, sleep apnea (SA) consists of 90% obstructive and only 10% central events [35].…”
mentioning
confidence: 99%
“…Similarly, Cologan and colleagues proposed that the presence of EEG patterns resembling normal human sleep [9] (i.e. well-structured patterns of non rapid eye movement and/or rapid eye movement (REM) sleep)can be markers of a favorable outcome after brain injury [10]. Moreover, the quality and quantity of spindles can provide a new index of the severity of thalamocortical injury, in accordance with brain imaging studies showing the correlation between the extent of thalamus damage and behavioral disability and outcome in disorders of consciousness [10][11][12][13].Gosselin and colleagues observed increased delta and decreased alpha activity during wakefulness in patients with mild TBI and proposed sleep intrusions in the waking state might indicate continuous sleep inertia, manifesting as fatigue and impaired functioning [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation